Is Salvinia natans (L.) a Water Quality Improver? - Wang, Jinqi; Zheng, Youfei; Wang, Guoxiang (Asian Journal of Chemistry, 2013)
S. natans (L.) is a free-floating aquatic plant in freshwater bodies. The impact of S. natans (L.) on water quality is tested in natural waters. A natural water body is divided into some regions and two similar regions are used to experiment. S. natans (L.) is planted and the water quality is monitored regularly and analyzed. This showed that the water quality during the growing season is not only improved in planted S. natans (L.) significantly, but also the capacity of re-oxygenation is reduced remarkably because of S. natans (L.) covering the water surface. Thus dissolved oxygen content of the experiment water body is lower than the control water body and affecting the conversion of various elements in the experiment water body. When the plant coverage exceeds 80 %, S. natans (L.) will affect the re-oxygenation capacity significantly, photo permeability ability, result in the dissolved oxygen concentration reduction and affect other aquatic organisms activities, the nitrogen and phosphorus content is increased rapidly in water body, so lead the water quality to deterioration, but permanganate index is affected minor. The water quality indexes restores the similar level with the control until Salvinia natans (L.) died and subsided to the sediment. Salvinia natans (L.) may pollute the water body after death and decompose at a short-term if Salvinia natans (L.) grows a large-scale and absorbs many nutrients from the sky and water. So Salvinia natans (L.) can't improve the water quality at their live period, on the contrary conduces the water quality deterioration. The ecological restoration careful selects the Salvinia natans (L.) as purification species in eutrophic water, the growth trend of Salvinia natans (L.) is closely monitored, the Salvinia natans (L.) coverage must be controlled and must be reaped by period.